Ergonomic and Biomechanical Analysis of the Manioc Root Harvest: Case Report (Human Factors in Design, 2020)
The aim of this case report was to evaluate the risks of musculoskeletal injuries from manual extraction of manioc roots in a Brazilian family farming production. It was used a lumbar extension isometric dynamometry, electromyography and infrared thermography of the surface at the back of the worker and the whole collection of data was made in loco. The results showed an increased temperature on the surface of the left lower back (+0.6 ℃), the values of isometric strength upon lumbar extension (143 ± 2.66 Kgf) and electromyography alteration in the muscles. The questionnaires indicate that the individual complains of discomfort along all of the back of his torso. The activity of manioc manual extraction can generate an overload on the lumbar and shoulder girdle muscles. It can affect the individual productive state.
Keywords: Family agriculture; Manioc; Ergonomics; Biomechanics; Musculoskeletal Disorders